2008
DOI: 10.1029/2007gl032837
|View full text |Cite
|
Sign up to set email alerts
|

Lability of DOC transported by Alaskan rivers to the Arctic Ocean

Abstract: [1] Arctic rivers transport huge quantities of dissolved organic carbon (DOC) to the Arctic Ocean. The prevailing paradigm is that DOC in arctic rivers is refractory and therefore of little significance for the biogeochemistry of the Arctic Ocean. We show that there is substantial seasonal variability in the lability of DOC transported by Alaskan rivers to the Arctic Ocean: little DOC is lost during incubations of samples collected during summer, but substantial losses (20 -40%) occur during incubations of sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
339
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(389 citation statements)
references
References 28 publications
19
339
4
Order By: Relevance
“…This is consistent with results from studies in other subarctic and arctic rivers (Striegl et al, 2005Raymond et al, 2007;Walvoord and Striegl, 2007;McNamara et al, 2008;Frey and McClelland, 2009;Guo et al, 2012). The DOC mobilized during high f low events is generally believed to be of modern age (Guo and Macdonald, 2006;Neff et al, 2006) and part of the DOC transported during spring melt may be labile (Holmes et al, 2008). Where changes in permafrost extent are sufficient to alter f lowpaths, the carbon balance of subarctic watersheds could shift from a net sink to a net source Grosse et al, 2011).…”
Section: Interior Alaska Wetlands and Hydrogeologysupporting
confidence: 79%
“…This is consistent with results from studies in other subarctic and arctic rivers (Striegl et al, 2005Raymond et al, 2007;Walvoord and Striegl, 2007;McNamara et al, 2008;Frey and McClelland, 2009;Guo et al, 2012). The DOC mobilized during high f low events is generally believed to be of modern age (Guo and Macdonald, 2006;Neff et al, 2006) and part of the DOC transported during spring melt may be labile (Holmes et al, 2008). Where changes in permafrost extent are sufficient to alter f lowpaths, the carbon balance of subarctic watersheds could shift from a net sink to a net source Grosse et al, 2011).…”
Section: Interior Alaska Wetlands and Hydrogeologysupporting
confidence: 79%
“…It has been suggested that warming will increase mobilization of soil DOC and DON due to exposure of previously frozen organic material (Frey et al 2007a;Frey and McClelland 2009). This change might not be reflected in DOC and DON concentrations, since this material is rapidly consumed in the stream, especially during spring snowmelt (Holmes et al 2008). In other words, an increase in export of terrestrial organic matter combined with rapid in-stream transformations of DOC and DON might be responsible for the observed increase in NO 3 -concentrations.…”
Section: Changes In C and N Flux In The Kuparuk Rivermentioning
confidence: 99%
“…2b, respectively). The solid lines and symbols represent samples taken during the rising hydrograph, and the open symbols and dashed lines represent samples taken during the falling hydrograph Biogeochemistry (2011) 103:109-124 117 Kuparuk River showed that 20-40% of the DOC transported by rivers in the early spring is microbially available, while late-summer DOC is much less labile (Holmes et al 2008). Seasonally varying UV photolysis (Wetzel et al 1995) may also contribute to changes in discharge-specific DOC concentrations as the summer progresses.…”
Section: Seasonal Variations In Constituent Exportmentioning
confidence: 99%
“…About 17 % of the DOC was reported to be biologically available in lake, river, and marine ecosystems (Sondergaard and Middelboe, 1995). Recently, studies have shown that a significant fraction (∌ 30 %) of Arctic river DOC is degradable in the Arctic Ocean on a scale of 1-2 years (Alling et al, 2010;Holmes et al, 2008) -longer than the shallow shelf water residence time, which is on the order of several weeks (Nikiforov and Shpaikher, 1980;Semiletov et al, 2000). Thus, in the near-shore zone, riverine DOC can be considered a quasiconservative parameter.…”
Section: Biogeochemical Signatures Of Organic Matter Degradation In Smentioning
confidence: 99%